Novel formulation of bio-adhesive using natural rubber latex and starch for wood composite industry - Gupta, Arun; Thuraisingam, Jasyhree; R. M., Yunus; Nurlisa Syahiera, Mohd Rapidi (2018)
Adhesives play a very crucial role in determining the end product quality in wood composite industry. Strong adhesive joints resemble greater mechanical properties of the wood panels, and therefore, selection of adhesives in the manufacturing of particleboard, MDF and plywood really accounts for the rise or fall of the industry. Conventionally, formaldehyde based resins are widely used as adhesives in the manufacturing of wood panel, by which urea formaldehyde (UF), tops the preference among the wood composite manufacturers. UF based adhesive applications on the wood composites tend to endanger human lives through subsequent formaldehyde emission into the air. Due to that limitation, bio-adhesive which is renewable, cheaper, possess greater mechanical properties in terms of stronger adhesion properties as well as with zero formaldehyde emission is vital to be discovered in the upcoming years so that consumers’ health will not be sacrificed at any extent. Hence, this project portrays the potential of bio-adhesive development from natural Rubber latex and rice starch. By the application of new adhesive, the mechanical properties were comparable to the market standard. It will also not emit any toxic emissions, thus no health problems.